Pengaruh Good Corporate Governance, Solvabilitas dan Profitabilitas Terhadap Harga Saham pada Sektor Makanan dan Minuman - Jambarati Roselin; Basuki Rahmanto (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2023)
This study aims to determine the effect of good corporate governance solvency and profitability on stock prices of the food and beverage sub-sector. The independent variables studied were good corporate governance, solvency and profitability as proxied by managerial ownership. institutional ownership. DER and ROA. The population is the food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the 2015-2021 period. The sample was selected using a purposive sampling technique, in order to obtain i19 companies that meet the criteria as a sample. data analysis was performed using panel data regression analysis method. The research shows that Managerial Ownership. Institutional Ownership and ROA have an effect on stock prices. Meanwhile, iDER has no effect on stock prices.